Penerapan Etika Digital di Kalangan Content Creator TikTok - Pramesti, Olivia Lewi (MediaTor (Jurnal Komunikasi), 2022)
Content creator is becoming an in-demand profession for the millennial generation, along with increased social media consumption in Indonesia. Content creators do not just upload content but are required to create creative content. These content creators can be called citizen journalists because they perform media functions, including providing information, mobilizing, entertaining, and spreading values to society. Content creators are also required to be professional. Professional means content creators not only create creative content but also need to pay attention to digital ethics. This study will look at the application of digital ethics among TikTok content creators. Digital ethics is essential because this moral guide will help content creators reflect on uploaded content. This study uses qualitative research with a case study method. The results show that content creators do not fully understand digital ethics principles. Digital ethics was only discovered after the informant received punishment from TikTok for the uploaded content. Furthermore, this study shows that content creators are more dominant in practicing device literacy than digital ethics.